2017
DOI: 10.3762/bjoc.13.124
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of elansolids B1 and B2

Abstract: The elansolids A1–A3, B1, and B2 are secondary metabolites formed by the gliding bacterium Chitinophaga sancti. They show antibacterial activity against Gram-positive bacteria. A second generation total synthesis of the antibiotic elansolid B1 (2) and the first synthesis of elansolid B2 (3) are reported. In contrast to previous work, the (Z,E,Z)-triene at C10–C15 was assembled by using an optimized C–C cross-coupling sequence with a Suzuki cross-coupling reaction as key step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The elansolids are a family of polyketide antibiotics from the gliding bacteria Chitinophaga sancti. Initially, alongside the original atropoisomers elansolids A1/A2 ( 2 ), the derivatives elansolid B1 ( 3 ), B2 ( 4 ), and B3 (not shown) were identified in the bacterial fermentation extract (Figure ). …”
Section: Categories Of Nonenzymatic Mechanismssupporting
confidence: 66%
“…The elansolids are a family of polyketide antibiotics from the gliding bacteria Chitinophaga sancti. Initially, alongside the original atropoisomers elansolids A1/A2 ( 2 ), the derivatives elansolid B1 ( 3 ), B2 ( 4 ), and B3 (not shown) were identified in the bacterial fermentation extract (Figure ). …”
Section: Categories Of Nonenzymatic Mechanismssupporting
confidence: 66%
“…Concerning the construction of the chiral polyene chain, Kirschning planned to use the (2 S ,3 S ) chirality within aldehydes 414 (representing the fragment C7–C11) to control the absolute R -configuration of the newly formed stereogenic center at C7, with the aid of the Yamamoto protocol. 296 298 …”
Section: Vinylogous Esters and Lactonesmentioning
confidence: 99%
“… The core structure of these natural polyketides features a bicyclo[4.3.0]­nonane unit embedding a chiral polyene chain resulting in a macrolactone core in elansolids A1 and A2 or its linear seco -acid form in elansolids B1 and B2. Concerning the construction of the chiral polyene chain, Kirschning planned to use the (2 S ,3 S ) chirality within aldehydes 414 (representing the fragment C7–C11) to control the absolute R -configuration of the newly formed stereogenic center at C7, with the aid of the Yamamoto protocol. …”
Section: Vinylogous Esters and Lactonesmentioning
confidence: 99%
“…The total chemical synthesis of elansolid B1 (4) 26 was followed by the second-generation total synthesis of the same compound and the rst synthesis of elansolid B2 (5). 27 Further studies to elucidate the biosynthesis of elansolids 28,29 revealed a further polyketide, 20-deoxy-elansolid B1 (10), with activity similar to elansolid A2 (2), showing that the hydroxyl group at C20 is not essential for antibacterial activity. 28…”
Section: Elansolidsmentioning
confidence: 99%